Implications of gamification and virtual reality in higher education - Bilro, R.G.; Loureiro, S. M. C.; Angelino, F. J. (Managerial challenges and social impacts of virtual and augmented reality, 2020)
Gamification and virtual reality are becoming more common in higher education, leading to more research toward this topic and its applications. Following this new trend, this chapter identifies and proposes practical applications and future directions for gamification and virtual reality in higher education environments. Authors contribute with precise inputs how to create student engagement and motivation towards learning and academic activities. Future research avenues in these domains are given. Authors draw conclusions about future changes in the educational experiences through gamification and virtual reality.